Political parties and MPs’ morality policy voting behaviour: evidence from Germany - Engler, Fabian; Dümig, Kathrin (Parliamentary affairs, 2017)
Abstract. This article investigates the impact of party membership on MPs’ morality policy voting behaviour, going beyond the common dichotomy of left and righ
Advance access publication 24 December 2016
Gesehen am 07.11.2018